2005
DOI: 10.1300/j052v24n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Issues Related to Satisfaction with Food and Food Service in the Nursing Home from the Resident's Perspective

Abstract: This paper reviews organizational factors that potentially affect food quality and food service in the nursing home. A model is proposed for assessing the influence of organizational technology on resident satisfaction with food and food service from the resident's perspective. Findings from an exploratory phenomenological case study applying the model are presented. Staff knowledge of how to prepare and serve food properly, and staff availability to serve food on time, were key constructs. Resident-staff inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Chang and Roberts (31) also reported that of the 31 nursing assistants they interviewed and observed during meals in a Taiwanese nursing home, 93% felt there wasn't enough staff and they lacked the knowledge needed to feed residents well. Further, a study focusing on residents' perspectives found that residents felt there were inadequate staff numbers to cook food properly, assist them during meals, monitor their intake, and return them to their rooms after eating (32).…”
Section: Inadequate Staffingmentioning
confidence: 99%
“…Chang and Roberts (31) also reported that of the 31 nursing assistants they interviewed and observed during meals in a Taiwanese nursing home, 93% felt there wasn't enough staff and they lacked the knowledge needed to feed residents well. Further, a study focusing on residents' perspectives found that residents felt there were inadequate staff numbers to cook food properly, assist them during meals, monitor their intake, and return them to their rooms after eating (32).…”
Section: Inadequate Staffingmentioning
confidence: 99%
“…Older persons prefer a traditional diet (Crogan et al, 2004;Shultz et al, 2005;Wikby & Fägerskiöld, 2004). Dissatisfaction appears when the meal differs from what they were used to eating at home.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…If the food tastes good, is carefully prepared and fulfils expectations, then the residents will enjoy it. Appetite increases when the residents can maintain their familiar eating habits (Shultz et al, 2005;Wikby & Fägerskiöld, 2004).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations